1984
DOI: 10.1021/jo00189a017
|View full text |Cite
|
Sign up to set email alerts
|

Product studies of the photocycloaddition reactions of 5-chloro- and 5-fluorouracil derivatives and olefins. An interesting and useful effect of fluorine on regioselectivity

Abstract: earlier procedure. With the more reactive aromatics, p-dimethoxybenzene and naphthalene, additional competitions employing 2:1 or 5:1 molar ratios of benzene to p-dimethoxybenzene or naphthalene were also run.Peroxide-Initiated Reactions. Chloroacetonitrile, (5 mmol), toluene (10 mmol), and the peroxide (5 mmol) were dissolved in acetonitrile (100 mL), degassed with nitrogen, and heated. The OO-tert-butyl isopropyl peroxycarbonate reactions were refluxed (80 °C) for one week whereas the di-n-propyl peroxydicar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…But when acetone was added into the reaction system, the reaction rate was increased dis- Similarly, whether acetone was added to the reaction mixture or not, the reaction products obtained were the same. They were 2,4,6-trimethyl-3,5-dioxo-7,8-bismethoxymethyl-l,2,4-triazabicyclo[4,2,0]-7-heptene (2) and 1,3,5-trimethyl-4-oxo-8,9-bismethoxymethyl--2,3,5-triaza-7-oxaspiro[5,3]-1,8-nonadiene (3). When acetone was added into the mixture the reaction was much faster.…”
Section: Phorocycloaddition Of Ly3-dimethyl-6-azathymine (Dmat) and 2mentioning
confidence: 99%
“…But when acetone was added into the reaction system, the reaction rate was increased dis- Similarly, whether acetone was added to the reaction mixture or not, the reaction products obtained were the same. They were 2,4,6-trimethyl-3,5-dioxo-7,8-bismethoxymethyl-l,2,4-triazabicyclo[4,2,0]-7-heptene (2) and 1,3,5-trimethyl-4-oxo-8,9-bismethoxymethyl--2,3,5-triaza-7-oxaspiro[5,3]-1,8-nonadiene (3). When acetone was added into the mixture the reaction was much faster.…”
Section: Phorocycloaddition Of Ly3-dimethyl-6-azathymine (Dmat) and 2mentioning
confidence: 99%
“…On the other hand, however, photochemical reactions of pyrimidine bases and nucleosides with simple olefins, though it would provide a basis for understanding their photolability, have unexpectedly received little attention. In the literature, a few studies have been reported by Swenton et al 9,10 and Kaneko and Shimomura 11 who have compared these reactions with photocycloaddition of α,β‐unsaturated carbonyl compounds, and by Charlton and Lai 12 who have studied on the reaction of uridine with 2,3‐dimethyl‐2‐butene (Bu). † No one has investigated the mechanistic aspects of these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[193][194][195][196] Later efforts also considered photodimerization of 5-FU as a useful synthetic approach to substituted pyrimidines and novel bicyclic nucleosides (Scheme 4.2b). [197][198][199] The photophysics behind the dimerization [200][201] and cleavage 202 of fluorouracil dimers and cycloadducts was also studied as interest in 5-FU was maintained through the last few Continued efforts by the group moved from the original backbone to a polymethacrylatebased block copolymer, wherein one block contained alkyl-ester side chains to produce a largely hydrophobic region of the polymer, the other block bearing side chains appended with the 4-methylcoumarin moiety, drastically increasing the number of available binding sites for the API (Scheme 4.3). 204 The resulting polymer formed micelles in a water/THF co-solvent system and was conjugated to 5-FU under long-wave UV.…”
Section: Discussionmentioning
confidence: 99%
“…We note that UV-irradiation of 5-FU in solution produces photodimers only in the presence of a sensitizer, 196 while CPRs of 5-FU in solution are quite limited (e.g. coumarin) [197][198][199] yet are gaining interest in drug delivery. 202,204 Our goal to form a solid 227 with a photoreactive API such as 5-FU would also, thus, provide a unique entry to pharmaceutical cocrystals 228 wherein the covalentbond-forming photoreaction may be useful for pharmaceutical applications.…”
Section: Chapter Overviewmentioning
confidence: 99%